Assessment of Hymenoptera and Non-Hymenoptera Insect Bite and Sting Allergy Among Patients of Tropical Region of West Bengal, India. Issue 1 (22nd June 2019) - Laha, Arghya; Sarkar, Tania; Dey, Debarati; Mondal, Priti; Bhattacharya, Srijit; Moitra, Saibal; Saha, Goutam Kumar; Podder, Sanjoy
Abstract: West Bengal, India, is inhabited by abundance and variety of insects that triggers sensitization in some humans to inhalant allergens and/or insect stings/venoms. Lack of research on this topic prevented accurate diagnosis and proper follow-up treatments to patients suffering from insect-induced allergies. The aim of our study was to identify the allergy-causing insects and evaluate resulting sensitization among a study population in West Bengal, India. The skin prick test (SPT) evaluated sensitivity of 450 patients who sought treatment at the Allergy and Asthma Research Center from July 2017 to June 2018. Eight insect allergens were tested: Common Black Ant ( Lasius niger, Linnaeus 1758), Fire Ant ( Solenopsis invicta, Buren 1972), Honey Bee ( Apis cerana indica, Fabricius 1798), Common Wasp ( Vespula vulgaris, Linnaeus 1758), Mosquito ( Aedes aegypti, Linnaeus in Hasselquist 1762), American Cockroach ( Periplaneta americana, Linnaeus 1758), House Fly ( Musca domestica, Linnaeus 1758), and Grasshopper (G esonula punctifrons, Stal 1861). From a total of 450 patients evaluated, 370 patients had positive SPT reaction from at least one of the 8 insect allergens tested. Sensitivity to some Hymenoptera insects (common black ant, 87.62%; fire ant, 84.59%; and honey bee, 67.02%) was found in higher proportion than non-Hymenoptera group (mosquito, 66.67%; American cockroach, 33.33%; house fly, 10.41%; and grasshopper, 5.14%). There was significant difference in sensitivity among child, adolescent, and adult ( P < 0.001). While female patients showed more sensitivity than males to SPT, the difference was statistically insignificant. In regards to occupation, farmers and bee keepers were most sensitive of field workers sensitive to Hymenoptera-derived allergens.